Expression, purification and molecular analysis of the human ZNF706 protein - Colombo, Jucimara [UNESP]; Provazzi, Paola Jocelan Scarin [UNESP]; Calmon, Marilia Freitas [UNESP]; Pires, Lilian Campos [UNESP]; Rodrigues, Nathália Campos; Petl, Paulo [UNESP]; Fossey, Marcelo Andrés [UNESP]; De Souza, Fátima Pereira [UNESP]; Canduri, Fernanda; Rahal, Paula [UNESP] (Springer Nature, 2013)
Background: The ZNF706 gene encodes a protein that belongs to the zinc finger family of proteins and was found to be highly expressed in laryngeal cancer, making the structure and function of ZNF706 worthy of investigation. In this study, we expressed and purified recombinant human ZNF706 that was suitable for structural analysis in Escherichia coli BL21(DH3). Findings. ZNF706 mRNA was extracted from a larynx tissue sample, and cDNA was ligated into a cloning vector using the TOPO method. ZNF706 protein was expressed according to the E. coli expression system procedures and was purified using a nickel-affinity column. The structural qualities of recombinant ZNF706 and quantification alpha, beta sheet, and other structures were obtained by spectroscopy of circular dichroism. ZNF706's structural modeling showed that it is composed of α-helices (28.3%), β-strands (19.4%), and turns (20.9%), in agreement with the spectral data from the dichroism analysis. Conclusions: We used circular dichroism and molecular modeling to examine the structure of ZNF706. The results suggest that human recombinant ZNF706 keeps its secondary structures and is appropriate for functional and structural studies. The method of expressing ZNF706 protein used in this study can be used to direct various functional and structural studies that will contribute to the understanding of its function as well as its relationship with other biological molecules and its putative role in carcinogenesis. © 2013 Colombo et al.; licensee BioMed Central Ltd.
Keywords: Circular dichroism; Cloning; HSPC038; Molecular modeling; Protein expression; ZNF706 protein